Design, validation, and reliability of survey to measure female athlete triad knowledge among coaches - Jillian E. Frideres; Sue G. Mottinger; José M. Palao (Universidade Estadual Paulista (UNESP), 2015)
The purpose of this study was to design and to test the validity and reliability of an instrument to evaluate coaches' knowledge about the female athlete triad syndrome and their confidence in this knowledge. The instrument collects information regarding: knowledge of the syndrome, components, prevention and intervention; confidence of the coaches in their answers; and coach's characteristics (gender, degree held, years of experience in coaching females, continuing education participation specific to the syndrome and its components, and sport coached). The process of designing the questionnaire and testing the validity and reliability of it was done in four phases: a) design and development of the instrument, b) content validity, c) instrument reliability, and d) concurrent validity. The results show that the instrument is suitable for measuring coaches' female athlete triad knowledge. The instrument can contribute to assessing the coaches' knowledge level in relation to this topic.